Water-in-CO2 Microemulsions Stabilized by an Efficient Catanionic Surfactant - Shirin Alexander (Langmuir, 2020)
To facilitate potential applications of water-in-supercritical CO2 microemulsions (W/CO2 μEs) efficient and environmentally responsible surfactants are required with low levels of fluorination. As well as being able to stabilize water–CO2 interfaces, these surfactants must also be economical, prevent bioaccumulation and strong adhesion, deactivation of enzymes, and be tolerant to high salt environments. Recently, an ion paired catanionic surfactant with environmentally acceptable fluorinated C6 tails was found to be very effective at stabilizing W/CO2 μEs with high water-to-surfactant molar ratios (W0) up to ∼50 (Sagisaka, M.; et al. Langmuir 2019, 35, 3445−3454). As the cationic and anionic constituent surfactants alone did not stabilize W/CO2 μEs, this was the first demonstration of surfactant synergistic effects in W/CO2 microemulsions. The aim of this new study is to understand the origin of these intriguing effects by detailed investigations of nanostructure in W/CO2 microemulsions using high-pressure small-angle neutron scattering (HP-SANS). These HP-SANS experiments have been used to determine the headgroup interfacial area and volume, aggregation number, and effective packing parameter (EPP). These SANS data suggest the effectiveness of this surfactant originates from increased EPP and decreased hydrophilic/CO2-philic balance, related to a reduced effective headgroup ionicity. This surfactant bears separate C6F13 tails and oppositely charged headgroups, and was found to have a EPP value similar to that of a double C4F9-tail anionic surfactant (4FG(EO)2), which was previously reported to be one of most efficient stabilizers for W/CO2 μEs (maximum W0 = 60–80). Catanionic surfactants based on this new design will be key for generating superefficient W/CO2 μEs with high stability and water solubilization.